Changes In Some Serum Enzymes And Urea Nitrogen In Neonatal Bovine Diarrheic Calves Of Different Age Groups (Applied Biological Research, 2015)
The present study was conducted on 100 cases of bovine calf diarrhea to  monitor the activities of some serum enzymes viz., AST, ALP, GGT, CK and urea nitrogen in neonatal calves of different age groups. These  calves were divided into 5 age groups viz., 1-7 day (7 calves), 8-14 days (5  calves), 15-21 days (30 calves), 22-30 days (19 calves) and 31-60 days (39  calves). The results of experimental groups were compared with normal  standard values of different age groups. The diseased calves of all the age groups had significantly higher (p
Keywords: Neonatal calf diarrhea; serum enzymes; urea nitrogen